2017
DOI: 10.3390/rs9060548
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Kernel Minimum Noise Fraction Transformation for Hyperspectral Image Classification

Abstract: This paper presents an optimized kernel minimum noise fraction transformation (OKMNF) for feature extraction of hyperspectral imagery. The proposed approach is based on the kernel minimum noise fraction (KMNF) transformation, which is a nonlinear dimensionality reduction method. KMNF can map the original data into a higher dimensional feature space and provide a small number of quality features for classification and some other post processing. Noise estimation is an important component in KMNF. It is often es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 59 publications
0
41
0
Order By: Relevance
“…However, MNF is unable to achieve reliable performances in real applications (Gao et al 2013b). Some work has reported that the fundamental reason constraining the transformation of MNF was inaccuracy in the calculation of NF (Greco 2006;Liu et al 2009;Gao et al 2011;Zhao, Gao and Zhang, 2016;Gao et al 2017). The information content for a particular hyperspectral image remains unchanged; the calculation accuracy of NF mainly depends on the noise estimation results.…”
Section: Open Accessmentioning
confidence: 99%
“…However, MNF is unable to achieve reliable performances in real applications (Gao et al 2013b). Some work has reported that the fundamental reason constraining the transformation of MNF was inaccuracy in the calculation of NF (Greco 2006;Liu et al 2009;Gao et al 2011;Zhao, Gao and Zhang, 2016;Gao et al 2017). The information content for a particular hyperspectral image remains unchanged; the calculation accuracy of NF mainly depends on the noise estimation results.…”
Section: Open Accessmentioning
confidence: 99%
“…Hyperspectral sensors have attracted much interest in remote sensing for providing abundant and valuable information over the last few decades. With the useful information, HSI has played a vital role in many applications, among which classification [5][6][7] is one of the crucial processing steps that has received enormous attention. The foremost task in hyperspectral classification is to train an effective classifier with the given training set from each class.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, hyperspectral images require preprocessing to reduce spectral bands [3,4] and denoising prior to further processing. Many techniques have been applied in hyperspectral data analysis to reduce data dimensionality, including selection-based [5] and transformation-based techniques [6] such as Independent Component Analysis (ICA).…”
Section: Introductionmentioning
confidence: 99%